Hubungan Antara Kompetensi Guru Dengan Perkembangan Sosial Anak di TK Aisyiyah Kecamatan Boyolali 2015/2016 - Nugraheni, Wahyu, Drs. Haryono Yuwono, M.Pd (2016)
Early Childhood Education is an important step for the child. On the early age the brain child is growing rapidly so that the teaching given in the early age is very useful for further development. This period is an important period for cultivation of the virtues (basic goodness) in individual that constructs her an individual character. Teachers or educators assist the growth and the development of children physically and mentally in order to have the readiness to the further education. This study was supposed to identify the relationship between teachers face the competence and social development of children in Aisyiyah kindergarten Boyolali District of 2015/2016. This research used descriptive quantitative research. This research was conducted in the District Boyolali Aisyiyah kindergarten for children aged 5-6 years in the academic year 2015/2016. The research sample was 34 children, they were children from Aisyiyah 1 kindergarten, 12 children from Aisyiyah 2 kindergarten and 9 children from Aisyiyah 3 kindergarten. The sampling used proportional random sampling. The data collection method used hypothesis product moment correlation analyst. Based on the analysis it was found that there was a relationship between the teacher competence on social development of children in Aisyiyah kindergarten Boyolali of 2015/2016. This was evidenced by the results of Pearson correlation r of 0938 with significant 0,000 <0.05 (p = 0.000; p <0.05), which meant Ho was rejected. It can be counded that there was a correlation between the competence of teachers to the social development of children in Aisyiyah kindergarten in Boyolali 2015 / 2016.